Dual-organ transplantation in older recipients: outcomes after heart–kidney transplant versus isolated heart transplant in patients aged ≥65 years†. (3rd July 2018) - Reich, Heidi; Dimbil, Sadia; Levine, Ryan; Megna, Dominick; Mersola, Savannah; Patel, Jignesh; Kittleson, Michelle; Czer, Lawrence; Kobashigawa, Jon; Esmailian, Fardad
Abstract: OBJECTIVES: Combined heart–kidney transplantation has successful outcomes. With an increasing number of patients with end-stage heart disease, there is a high incidence of significant renal insufficiency that may necessitate combined heart–kidney transplant. Outcomes for heart–kidney transplant recipients aged ≥65 years are not well described. METHODS: Between 2010 and 2015, 163 recipients ≥65 years of age were transplanted in a single centre: 12 heart–kidney and 151 isolated heart transplants. Outcomes assessed were estimated glomerular filtration rate at 1, 6 and 12 months after transplant, the need for dialysis, 1-year survival, 1-year freedom from rejection, 1-year freedom from cardiac allograft vasculopathy and 1-year freedom from non-fatal major adverse cardiac events. RESULTS: Recipient ages were 67.8 ± 1.6 and 69.0 ± 2.8 years for heart–kidney transplant and isolated heart transplant, and pretransplant estimated glomerular filtration rates were 26.6 ± 9.4 vs 55.2 ± 18.9, respectively. At 1 month (66.3 ± 31.4 vs 67.2 ± 28.0, P  = 0.92), 6 months (68.1 ± 21.3 vs 60.5 ± 19.6, P  = 0.20) and 12 months (58.6 ± 21.5 vs 52.4 ± 18.5, P  = 0.27) post-transplant, estimated glomerular filtration rate was similar for heart–kidney transplant versus isolated heart transplant. There was a trend towards reduced 1-year freedom from temporary dialysis after heart–kidney transplant relative to isolated heart transplant (75.0% vs 90.4%, P  = 0.06) without a difference in 1-year freedom from chronic dialysis (100% vs 95.2%, P  = 0.46). There were no differences in 1-year survival, 1-year freedom from any treated rejection, acute cellular rejection, antibody-mediated rejection, cardiac allograft vasculopathy and non-fatal major adverse cardiac events. CONCLUSIONS: For patients ≥65 years old, heart–kidney transplant can achieve outcomes on par with heart transplant alone.